2002
DOI: 10.1046/j.1365-2249.2002.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal dendritic cells are intrinsically biased against Th-1 immune responses

Abstract: SUMMARYDendritic cells (DCs) were derived from human peripheral blood monocytes or cord blood monocytes cultured in the presence of IL-4 and GM-CSF. Adult and cord DCs were observed to have comparable immature phenotypes. However, the increase in surface expression of HLA-DR and CD86 after addition of LPS was significantly attenuated in cord DCs, with CD25 and CD83 expression also markedly reduced. Cord DCs were also unable to produce IL-12p70, failed to down-regulate expression of the chemokine receptor CCR5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
136
1
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 33 publications
12
136
1
6
Order By: Relevance
“…However, in these studies allogenic cells from adult donors were used, whereas we used autologous cord blood cells, which is likely to explain the discrepant data. In line with our results, several groups have demonstrated the inability of neonatal cells to produce IFN-c relative to adult cells [25,27], whereas IL-13 production has been shown to be easily induced in cord blood cells after both polyclonal activation (anti-CD3, PHA) and allergen stimulation (blactoglobulin and Der p 1) [28]. In fact, IL-13 seems to be the dominant Th2 cytokine in neonatal T cells by which only low levels of IL-4 and IL-5 are secreted [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in these studies allogenic cells from adult donors were used, whereas we used autologous cord blood cells, which is likely to explain the discrepant data. In line with our results, several groups have demonstrated the inability of neonatal cells to produce IFN-c relative to adult cells [25,27], whereas IL-13 production has been shown to be easily induced in cord blood cells after both polyclonal activation (anti-CD3, PHA) and allergen stimulation (blactoglobulin and Der p 1) [28]. In fact, IL-13 seems to be the dominant Th2 cytokine in neonatal T cells by which only low levels of IL-4 and IL-5 are secreted [29].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that APC from cord blood, such as monocytes and DC, are not able to produce IL-12 after bacterial stimulation [24][25][26]. This might be explained by the fact that the IL-12 (p35) gene expression is highly repressed in LPS-stimulated neonatal DC compared to adult DC.…”
Section: Discussionmentioning
confidence: 99%
“…This peculiar sensitivity is associated with impaired Th1 cell responses [1]. We previously demonstrated that besides specific CD4 + T cells limitations in newborns, the Th1 cell default is at least partially explained by a markedly decreased production of IL-12(p70) by neonatal DC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies in mice also conflict because neonates produce either lower (17,18) or higher (19) levels of TNF compared with adults. The most consistent observation, however, is that the ratio of IL-6 to TNF is higher, whereas IFN-␥ is defective in neonates (10,11,20). However, whether and how these changes of proinflammatory cytokines will have any impact in vivo in response to infection or TLRs stimulation has not been well defined.…”
mentioning
confidence: 99%